Host-Pathogen Interactions in Streptococcal Diseases - Chhatwal, G Singh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Streptococci are Gram-positive bacteria that cause a wide spectrum of diseases, such as pharyngitis, necrotizing fasciitis and streptococcal toxic shock syndrome, as well as rheumatic fever and rheumatic heart disease as sequelae. Antibiotics alone have not been able to control the disease and in spite of many efforts an effective vaccine is not yet available. A prerequisite for novel and successful strategies for combating these bacteria is a complete understanding of the highly complex pathogenic mechanisms involved, which are analyzed in this volume. In ten chapters, prominent authors cover various aspects including streptococcal diseases and global burden, epidemiology, adaptation and transmission, and molecular mechanisms of different diseases, as well as sequelae, vaccine development and clinical management. This book will serve as a valuable reference work for scientists, students, clinicians and public health workers and provide new approaches to meeting the challenge of streptococcal diseases.
Group A Streptococcal Diseases and Their Global Burden -- Molecular Markers for the Study of Streptococcal Epidemiology -- Epidemiology and Pathogenicity of Zoonotic Streptococci -- Adherence and Invasion of Streptococci to Eukaryotic Cells and Their Role in Disease Pathogenesis -- Common Regulators of Virulence in Streptococci -- Host-Pathogen Interactions in Streptococcal Immune Sequelae -- Immunopathogenesis of Streptococcal Deep Tissue Infections -- Modulation of the Coagulation System During Severe Streptococcal Disease -- Group A Streptococcal Vaccine Candidates: Potential for the Development of a Human Vaccine -- Clinical Management of the Most Common Group A β-Hemolytic Streptococcal Infections.
Keywords: Medical microbiology; Immunology; Vaccines; Molecular biology; Public health; Bacteriology; Medical Microbiology; Immunology; Vaccine; Molecular Medicine; Public Health; Bacteriology